Box Behken design for optimization of COD removal from Palm oil mill effluent (POME) using Reverse osmosis (RO) membrane - Muhammad Said; Muneer ba Abbad; Siti Rozaimah Sheik Abdullah; Abdul Wahab Mohammad (Indonesian Journal of Environmental Management and Sustainability, 2019)
The optimization of COD removal from palm oil mill effluent (POME) using the Reverse Osmosis (RO) membrane was investigated. Experimental conditions for reduce the COD value of POME were achieved successfully using the Box Behken design. The values of affecting factors (POME concentration, pH and Transmembrane pressure were optimized according to the polynomial regression model. The predicted conditions to produce lower COD values were found to be POME concentration (vol. %) =28.30, pH =10.75 and Transmembrane pressure= 0.69 kPa. The predicted of COD value was 24.137 mg/l which in good agreed with experiment value as 25.763 mg/l was obtained.